Elements in school principalship: The changing role of pedagogy and the growing recognition of emotional literacy - Schneider, Alexander; Yitzhak-Monsonego, Einat (International Journal of Child, Youth and Family Studies, 2020)
This paper examines the changing role of pedagogy and the growing recognition of emotional literacy as an element in school principalship, as perceived by school principals. A model of the “principal’s toolkit” based on three “pillars” of leadership, management, and pedagogy was used, but with the addition of a fourth pillar, emotional literacy. Here we report on a survey of 63 principals and educational executives that was designed to examine principals’ views regarding which tools are required for school principalship, the way they prioritize those tools, and the weight accorded to each. The survey, which took place from September 2009 to July 2010, was conducted through a questionnaire and interviews. Quantitative processing of the questionnaire results was performed, as was content analysis of the open questions and the interviews. The findings clearly define and rate the components of the essential toolkit for principalship as perceived by the principals. Leadership and emotional literacy were rated highest and pedagogy and management lower, which is at odds with the prevailing attempt by the Israeli Ministry of Education to establish pedagogical leadership as the central element in principalship. This paper will explore and explain the phenomenon of change in principalship elements that entails the changing role of pedagogy and the increasing importance of emotional literacy as an element in school principalship.